2013
DOI: 10.1161/strokeaha.113.001738
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Microvascular Changes and Risk of Stroke

Abstract: Background and Purpose-To examine the relationship between retinal microvascular measures and incident stroke in an Asian Malay population. Methods-We conducted a prospective, population-based cohort study of Asian Malay persons 40 to 80 years at baseline.Retinal microvascular signs were assessed from baseline retinal photographs including quantitative retinal microvascular parameters (caliber, branching angle, tortuosity, and fractal dimension) and qualitative retinopathy signs. Incident stroke cases were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
105
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 39 publications
2
105
1
Order By: Relevance
“…The Singapore Malay Eye Study (SMES) also reported as association between baseline retinopathy and incident stroke during 4 years of follow up and developed models that improved upon those based on vascular risk factors by incorporating retinal vascular parameters. (5) These models improved classification of stroke outcome by 10%.…”
Section: Relationship Between Chronic Retinal Microvascular Disease Amentioning
confidence: 95%
See 1 more Smart Citation
“…The Singapore Malay Eye Study (SMES) also reported as association between baseline retinopathy and incident stroke during 4 years of follow up and developed models that improved upon those based on vascular risk factors by incorporating retinal vascular parameters. (5) These models improved classification of stroke outcome by 10%.…”
Section: Relationship Between Chronic Retinal Microvascular Disease Amentioning
confidence: 95%
“…En face images also permit analysis of vessel tortuosity,(4) fractal dimension and branching angles. (5) Focal thinning of retinal layers, as can be measured with OCT, may be a marker of prior vascular events causing ischemia. These analysis methods require high quality images and specialized analysis capabilities, which may not be available in the clinical setting.…”
Section: Methods Of Retinal Vessel Analysismentioning
confidence: 99%
“…Changes in retinal vascular calibre may also represent an individualised indicator of how well diabetes is controlled [100]. Recent studies in the general population have demonstrated that the addition of retinal vascular imaging to existing models of stroke can improve risk stratification [101,102]. However, the overall improvement is only about 10% beyond that of established risk factors.…”
Section: Retinal Vasculature Measurements In Clinical Practicementioning
confidence: 99%
“…We have previously used the database for other studies. 21,22 MI was defined as either (1) definitive or clinical MI; or (2) death cases signed up by pathologists or physicians as MI, with or without necropsy done. Incident MI was identified by linkage with a subset of the National Registry of Diseases Office database: the Singapore Myocardial Infarction Registry, which captures all MI diagnosed and coded with International Classification of Diseases 9th Revision (ICD-9) 410 in all hospitals.…”
Section: This Ismentioning
confidence: 99%